Navigating norms: a qualitative exploration of factors shaping contraceptive use in Senegal - Reveiz, Manuela; Gueye, Rahmatoulah; González Capella, Thaïs; Fall, Marieme; Horanieh, Nour; Larson, Elizabeth; Cislaghi, Beniamino (Frontiers in Global Women's Health, 2025)
IntroductionDespite the increasing contraceptive, women in Senegal are facing both material and social obstacles to access family planning (FP) services. Decisions regarding contraceptive use involve an interplay of influencers, including the woman, her partner, family members, healthcare providers, and the social norms in place. This study employs social norms theory to explore how these dynamics shape women's contraceptive choices, examining the societal expectations, influential relationships, and strategies women use.MethodsThis qualitative study involved 256 participants (130 men and 126 women) from four regions of Senegal (Dakar, Tambacounda, Ziguinchor, and Matam). We employed semi-structured interviews (116) and focus group discussions (16 FGDs with 8–10 participants each) to explore experiences related to family planning access and services. Participants were recruited through purposive sampling. Thematic analysis was performed using NVivo 12 Pro.ResultsParticipants highlighted how social norms on marriage, infertility, and childbearing heavily influence women's contraceptive use decisions. Participants also mentioned social norms that directly discouraged contraception use, labeling women who used it as disloyal or unloving. The failure to fulfill normative expectations resulted in various forms of sanctions. Given the normative system, numerous women opted to make decisions regarding childbearing in secrecy. Finally, a system of beliefs that participants held about religion and healthcare providers intersected with contraceptive utilization.DiscussionOur findings provide evidence of the importance of integrating social interventions into FP interventions to help reframe social relations. Three policy implications arise: (1) Addressing broader social needs and support mechanisms. (2) Integrating insights from violence against women research and theories on the dynamics of abuse into FP programs. (3) Integrating men further into FP programming to address misconceptions.ConclusionDrawing on data from 256 young people, men, and women of reproductive age, we uncovered how women navigate the terrain of social norms within their networks, shaping their choices concerning contraceptive utilization.